Factors influencing the movement of copper price on London metal exchange - Ngang, Mee Foong (Universiti Malaysia Sarawak (UNIMAS), 2010)
(This research is to understand the factors influencing the movement of copper price on LME in order to increase the competitiveness, reduce the risk, and improve the project management and reduce the losses from price volatilitv Three variables are (copper stock level, aluminium price, and exchange rate) being identified as the possible factors influencing the movement of copper price on LME. Theory of price formation of copper had determined the factors for the copper price formation. However, as this study focuses on how stock level, aluminium price (price of a substitute) and exchange rate influence the movement of copper LME price, it will use the inverse demand function of price formation ofcopper. The results of the study showed that all of these factors affecting copper price on LME. However, exchange rate influences to the copper price are lesser when compared with copper stock level and aluminium price. Both of the copper stock level and aluminium price have a positive relationship to the copper price. However, exchange rate has a negative relationship to the copper price. From the normalized cointegrating vector test, it showed that stock level and aluminium price is positively influence to the copper price. Real Effective exchange rate is however negatively influence to the copper price. The result is in line with the theory regarding price formation of copper (Qd = f (P, Ps, GDP, Exch. Rate) by Tilton. In conclusion, the factors (copper stock level, aluminium price and exchange rate) that being identified in this study was found to have different degree of influence to copper LME price. By understanding the relationship of the factors with copper LME price, it could increase the competitiveness, reduce the risk, and improve the project management and reduce the losses from price volatility.